Salt partitioning and transport in polyamide reverse osmosis membranes at ultrahigh pressures - Kevin Pataroque; Jishan Wu; Jinlong He; Hanqing Fan; Subhamoy Mahajan; Kevin Guo; Jason Le; Kay Au; Li Wang; Ying Li; Eric M.V. Hoek; Menachem Elimelech (Journal of Membrane Science Letters)
Understanding salt and water transport mechanisms in reverse osmosis (RO) under high pressures and salinities is critical to advancing RO-based brine management technologies. In this study, we investigate the dependence of salt permeance and partitioning on feed salinity and applied pressure. Salt partitioning coefficients were determined using a novel high-pressure quartz crystal microbalance (QCM), and salt permeances were collected using a lab-scale high-pressure dead-end cell. Our results show that salt permeance decreases with respect to feed concentration, in contrast to conventional theories for charged RO membranes. We further show salt partitioning coefficients do not change with applied hydrostatic pressure but are dependent on feed salt concentration. We use non-equilibrium molecular dynamics simulations to show that these trends are explained by salinity and pressure-induced changes to the structure of the polyamide layer, namely osmotic deswelling and compaction. Changes in the polyamide layer thickness and pore size alter the frictional interactions of ions, affecting membrane performance at larger salinities and pressures. These results provide new insights on how structure-performance relationships affect salt transport at higher pressures.